2009
DOI: 10.4269/ajtmh.2009.80.179
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Perforation Caused by Schistosoma haematobium

Abstract: A 31-year-old woman from Cameroon was admitted to the University of Strasbourg Hospital in December 2007 with pelvic pain and fever that developed over three days. Her condition rapidly worsened and she underwent emergency exploratory celioscopy. Surgeons found peritoneal and retrouterine abscesses. The high rectum had a 4-cm perforation with infiltrated, friable, and irregular edges. A biopsy specimen of this pseudotumoral specimen showed many Schistosoma haematobium eggs with an inflammatory reaction surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A review of literature revealed only three cases of colonic perforation associated with intestinal schistosomiasis. 13 To our knowledge, jejunal perforation associated with schistosoma has not been previously reported.…”
Section: Case Historymentioning
confidence: 89%
See 1 more Smart Citation
“…A review of literature revealed only three cases of colonic perforation associated with intestinal schistosomiasis. 13 To our knowledge, jejunal perforation associated with schistosoma has not been previously reported.…”
Section: Case Historymentioning
confidence: 89%
“…Intestinal perforation is a very unusual complication of schistomiasis and, to date, only three cases of colonic perforation associated with schistosoma infection have been reported in English literature. 13 We report an unusual case of jejunal perforation in a South Korean patient, associated with adult worm of schistosoma. To our knowledge, small intestinal perforation associated with adult worm of schistosoma has not been previously reported in literature.…”
Section: Introductionmentioning
confidence: 98%
“…A similar process usually takes place after infection by S. haematobium , with the difference being that the females lay their eggs in the perivesical venous plexus and the eggs are eliminated with urine. Despite being typically associated with the urinary tract, S. haematobium has also been associated with the colorectum, with rectal perforation reported in the literature [6]. …”
Section: Discussionmentioning
confidence: 99%
“…1 Bowel obstruction has previously been reported in this patient population but, with the exception of a case from Kuwait of jejunal perforation, 2 a French case of rectal perforation, 3 and a case of sigmoid colonic obstruction resulting in perforation, 4 there are no recorded cases of large bowel perforation in an individual positive for human immunodeficiency virus (HIV) in the literature. We report an unusual cause of large bowel obstruction with associated perforation and discuss the etiology.…”
Section: Introductionmentioning
confidence: 90%